2011
DOI: 10.1029/2011jd015735
|View full text |Cite
|
Sign up to set email alerts
|

Records of sulfate and nitrate in an ice core from Mount Muztagata, central Asia

Abstract: Annually resolved ice core records of major soluble ions (Na+, NH4+, K+, Mg2+, Ca2+, Cl−, SO42−, and NO3−) covering the period 1907–2002 A.D. from Mount Muztagata in central Asia are presented in this paper. Time series of major ion concentrations generally exhibit very similar temporal trends except NO3− and NH4+. Statistical analyses show that the chemical composition in the Muztagata ice core is predominantly controlled by terrestrial dust inputs originating from the extensive arid and semiarid regions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 56 publications
2
33
0
3
Order By: Relevance
“…Matsuki et al, 2010). This link is supported by a large inventory of previous work: (i) measurements in Asia indicate that dust is a significant source of SO42, largely of anthropogenic origin which comes together with dust, in snow and glaciers (Wake et al, 1990; Kreutz et al, 2001; Zhao et al, 2011); (ii) a close association of SO42 with crustal matter was argued to explain the close relationship between SO42 and Ca 2+ in rain water in India (Satyanarayana et al, 2010); (iii) Zhang et al (2007) suggested that acids such as HCl react with windblown crustal particles to yield a high Mg 2+ /Cl – correlation in China; and (iv) dust surfaces have been shown to become coated with soluble species such as SO42, NO3, and Cl – (Desbouefs et al, 2001; Sullivan et al, 2007; Matsuki et al, 2010) leading to enhanced hygroscopic properties (Levin et al, 1996; Koehler et al, 2007; Crumeyrolle et al, 2008; Sorooshian et al, 2012). Correlations between similar subsets of species (crustal species, SO42NH4+NO3, and the combination of the latter two) have also been observed in other regions such as the Mediterranean, Turkey, India, Brazil, Mexico, and China (Al-Momani et al, 1997; Basak and Agha, 2004; Safai et al, 2004; Mouli et al, 2005; Baez et al, 2007; Zhang et al, 2007; Teixeira et al, 2008; Yi et al, 2010; Raman and Ramachandran, 2011).…”
Section: Discussionsupporting
confidence: 56%
“…Matsuki et al, 2010). This link is supported by a large inventory of previous work: (i) measurements in Asia indicate that dust is a significant source of SO42, largely of anthropogenic origin which comes together with dust, in snow and glaciers (Wake et al, 1990; Kreutz et al, 2001; Zhao et al, 2011); (ii) a close association of SO42 with crustal matter was argued to explain the close relationship between SO42 and Ca 2+ in rain water in India (Satyanarayana et al, 2010); (iii) Zhang et al (2007) suggested that acids such as HCl react with windblown crustal particles to yield a high Mg 2+ /Cl – correlation in China; and (iv) dust surfaces have been shown to become coated with soluble species such as SO42, NO3, and Cl – (Desbouefs et al, 2001; Sullivan et al, 2007; Matsuki et al, 2010) leading to enhanced hygroscopic properties (Levin et al, 1996; Koehler et al, 2007; Crumeyrolle et al, 2008; Sorooshian et al, 2012). Correlations between similar subsets of species (crustal species, SO42NH4+NO3, and the combination of the latter two) have also been observed in other regions such as the Mediterranean, Turkey, India, Brazil, Mexico, and China (Al-Momani et al, 1997; Basak and Agha, 2004; Safai et al, 2004; Mouli et al, 2005; Baez et al, 2007; Zhang et al, 2007; Teixeira et al, 2008; Yi et al, 2010; Raman and Ramachandran, 2011).…”
Section: Discussionsupporting
confidence: 56%
“…The Ca 2þ record used as a dust indicator from a Muztagh Ata ice core (retrieved at 7010 m a.s.l.) was relatively low during the 1950se60s (Zhao et al, 2011) when both EC and OC increased. This suggests that the higher EC concentrations are not caused by dust-induced analytical problems.…”
Section: Differences In Rbc and Ecmentioning
confidence: 94%
“…Anthropogenic sulfur emissions derived from fossil fuel (i.e., coal and crude oil) consumption by the former USSR and Eastern Europe show rapid decreases near the end of 1980s and the beginning of 1990s (Smith et al, 2011). A large decrease of sulfate in the 1990s has been detected in the ice core record from the Muztagh Ata glacier (Zhao et al, 2011). Acetate (CH 3 COO À ) and formate (HCOO À ), which originate from anthropogenic emissions, also show rapid decreases in the 1990s, according to the ice core record from the Tianshan mountains (Lee et al, 2003).…”
Section: Contribution Of Biomass Burningmentioning
confidence: 99%
See 2 more Smart Citations